Ejercicios de equilibrio estático en la postura corporal del niño - Mullo Naula, Wilson Hernán (2025)
Static balance is a motor skill that allows the maintenance of a constant posture without displacements in the human being. A regular practice of static balance exercises benefits the strength of the postural muscles, aligns the body and prevents probable muscular decompensations. In children, this practice is important because it positively influences the development of posture control. The research entitled “Static balance exercises in the child's body posture” determined the incidence of static balance exercises in the body posture of children in the seventh year of Basic Education of the Intercultural Bilingual Community Education Unit “Hualcopo Duchicela”. Therefore, this study focused on postural alterations in children, which could be derived from poor postural alignment over time. A quantitative research was carried out, with a descriptive and explanatory scope, field type, cross-sectional. By means of a quasi-experimental design, descriptive propositional level, the children were assessed through a pre and post intervention of a static balance exercise program that lasted 12 weeks. For this assessment, an application called APECS (Assessment of body posture) was used to calculate postural deviations. The results of this study highlighted that in a pre-intervention, degrees of head inclination, misalignment of the shoulders, knees or feet were evidenced. After the intervention, relevant improvements in postural alignment and body stability were evidenced, which demonstrated the effectiveness of the exercise program. This highlighted the importance of integrating programs focused on static balance exercises to improve body posture in the school curriculum and promote postural hygiene exercises as a prevention strategy. Finally, this research indicates that static balance exercises had a positive influence on children's body posture, reducing postural alterations and preventing infants from future alignment problems. This research is a basis for planning educational and therapeutic strategies that benefit the motor development and postural health of children.